Genetic diversity of the west European honey bee (Apis mellifera mellifera and A. m. iberica). 1. Mitochondrial DNA - Garnery, L.; Franck, P.; Baudry, E.; Vautrin, D.; Cornuet, J.M.; Solignac, M.
Variability of mitochondrial deoxyribonucleic acid (mtDNA)has been studied in 973 colonies from 23 populations of the west European honey bees (lineage M)using restriction profiles of a polymerase chain reaction (PCR)amplified DNA fragment of the COI-COII intergenic region. Although populations are almost always introgressed by two other mtDNA lineages (A and C), results confirmed that the original haplotypes in western Europe are those of mtDNA lineage M. Iberian populations (Apis mellifera iberica)are characterised by a extended cline between haplotypes A and M, the former being almost fixed in south Spain and Portugal, and the latter almost pure in northeastern populations. This introgression is most likely attributable to humans and is probably ancient. French populations (A. m. mellifera)exhibit various levels of introgression by the C mtDNA lineage. ntrogression is lather low in regions with a dominance of amateur bee-keeping while it reaches very high values in regions where professional bee-keepers regularly import foreign queens (mainly A. m. ligustica and A. m. caucasica). When discarding introgressed haplotypes, French populations group in two clusters, one for the northeastern part of France, and the other one for all other populations, including Swedish and northeastern Spanish populations.
Keywords: HONEY BEE; MITOCHONDRIAL DNA; PCR; INTROGRESSION